Identification of 5H-chromeno[3, 4-c]pyridine and 6H-isochromeno[3, 4-c]pyridine derivatives as potent and selective dual ROCK inhibitors. Issue 21 (1st November 2020) - Hu, Zilun; Wang, Cailan; Sitkoff, Doree; Cheadle, Nathan L.; Xu, Songmei; Muckelbauer, Jodi K.; Adam, Leonard P.; Wexler, Ruth R.; Quan, Mimi L.
Graphical abstract: Abstract: A novel series of 5 H -chromeno[3, 4- c ]pyridine, 6 H -isochromeno[3, 4- c ]pyridine and 6 H -isochromeno[4, 3- d ]pyrimidine derivatives as dual ROCK1 and ROCK2 inhibitors is described. Optimization led to compounds with sub-nanomolar inhibitory affinity for both kinases and excellent kinome selectivity. Compound 19 exhibited ROCK1 and ROCK2 IC50 of 0.67 nM and 0.18 nM respectively.